EFEKTIVITAS INQUIRY BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN LITERASI DAN NUMERISASI DI SEKOLAH TINGKAT DASAR - Akbar Haqul Yaqin (Abtadi : Jurnal Pendidikan Dasar, 2024)
The inquiry-based learning (IBL) model is an educational approach that places students at the center of the learning process, where they are actively involved in exploration, questioning, investigation, and discovering solutions to their problems. This research aims to evaluate the effectiveness of IBL in improving literacy and numeracy skills among elementary school students. Literacy encompasses the ability to read critically and understand information, while numeracy involves understanding mathematical concepts and skills in problem-solving. This research uses a qualitative approach with a literature study method, where data is obtained from various scientific articles, books, and relevant research reports. The study results show that IBL can enhance critical thinking, analytical skills, and a deep understanding of literacy and numeracy concepts compared to conventional learning models. Although it has many advantages, implementing IBL faces challenges such as the need for more time and limited resources, especially in procuring experimental tools. Therefore, it is recommended that teachers receive special training and adequate resource support to optimize the implementation of IBL in elementary schools